2021
DOI: 10.20944/preprints202111.0140.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular Typing and Antimicrobial Susceptibility Profiles of Streptococcus uberis Isolated From Sheep Milk

Abstract: Intrammary infections are a major problem for dairy sheep farms, and Streptococcus uberis is one of the main etiological agents of ovine mastitis. Surveys on antimicrobial resistance are still limited in sheep and characterization of isolates is important for acquiring information on resistance and for optimizing therapy. In this study, a sampling of 124 S. uberis isolates collected in Sardinia (Italy) from sheep milk was analysed by multilocus-sequence typing (MLST) and pulsed field gel electrophoresis (PFGE)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The aad-6 gene was detected in S. uberis and S. dysgalactiae species in dairy cows (Kaczorek et al 2017a). Another study reported that aminoglycoside-resistant Streptococcus isolates are negative for aad-6 genes (Rosa et al 2021). Our results indicate that only 6 S. uberis isolates carried the aad-6 gene, aligning with the inherent aminoglycoside resistance of Streptococcus strains.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…The aad-6 gene was detected in S. uberis and S. dysgalactiae species in dairy cows (Kaczorek et al 2017a). Another study reported that aminoglycoside-resistant Streptococcus isolates are negative for aad-6 genes (Rosa et al 2021). Our results indicate that only 6 S. uberis isolates carried the aad-6 gene, aligning with the inherent aminoglycoside resistance of Streptococcus strains.…”
Section: Discussionsupporting
confidence: 54%
“…The blaZ gene is frequently detected in France for S. uberis, lnuD for S. uberis, and S. dysgalactiae in Poland (Naranjo-Lucena and Slowey 2023). Detection of the blaZ gene has also been reported in sheep milk (Rosa et al 2021). However, we detected the blaZ gene in S. uberis isolates, and the lnu gene in one S. agalactiae isolate (3.1%), which is consistent with its reported low prevalence (Haenni et al 2018).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations